Electrical and mechanical self-healing membrane using gold nanoparticles as localized "nano-heaters". Issue 42 (12th October 2016) - Chen, Lei; Si, Liping; Wu, Feng; Chan, Shuk Ying; Yu, Puiyan; Fei, Bin
Abstract : The tri-layered membrane is capable of both structural and electrical healing at the same damaged location for multiple times. Abstract : Healable, electrically conductive membranes are essential for the fabrication of reliable electronic devices to reduce their replacement and maintenance costs. Here, we report the fabrication of a tri-layered, light-triggered healable and highly electrically conductive membrane by depositing reduced graphene oxide (rGO) and silver nanowires (Ag NWs) onto an electrospun fibrous composite of gold nanoparticle (Au NP) incorporated polycaprolactone (PCL). The obtained fibrous membrane (FM), denoted as Au@PCL x /rGO/Ag, has a highly conductive surface with sheet resistance as low as 11.5 Ω sq −1, and shows very good flexibility to repeated bending cycles. Under 532 nm light irradiation, selective self-healing is achieved in the FM via local heating generated by Au NPs. The FM is capable of healing both structural and electrical properties for multiple times without apparent loss of surface conductivity. This photothermal-responsive healable conductor may become a potential element for healable and intelligent optoelectronic devices.